Koli ritual - Mumbai Archive Project Team (Jio Institute, 2024)
According to Ramnath Keny, this photo likely captures a tribal ritual, possibly reflecting the Kolis community’s tribal origins, which underscore their status as early inhabitants of the Mumbai region.